KESIAPSIAGAAN MASYARAKAT DALAM PENANGGULANGAN BENCANA: KASUS DI KECAMATAN CANGKRINGAN KABUPATEN SLEMAN â DI YOGYAKARTA - Gunawan, Gunawan (Sosio Informa, 2014)
Community preparedness in Disaster management is a case study in the southern slopes of Mount Merapi, Cangkringan, Sleman District. This study aims to answer the question: 1) how to build a Community response preparedness; 2) how the existence of the Community preparedness. Data and information gathered from multiple sources with techniques: a) study the documentation; b) in-depth interviews; c) observation; and d) Focused Group Discussions (FGD). From a qualitative descriptive analysis be revealed that people on the slopes of the volcano, generally have a problem-solving method (coping strategy) and the value of the underlying behavior of people in touch with nature. Society and government have united to achieve human welfare. Cangkringan Action is evidence of; 1) the seriousness of the state in Disaster Risk Reduction; 2) consistency and accountability of the Republic of Indonesia for the ASEAN agreement, the Asian nations and peoples of the world in Disaster Risk Reduction Cangkringan Community preparedness model can be replicated in other locations that have a high enough level of vulnerability. However, within the Framework of the model replication, allocation of time and energy of the Community need to be considered. Mountainside communities generally do not have a fixed income, so they need to be compensated for the time and effort that should be productive for themselves and their families to participate invarious programs taken up.Keywords: community, preparedness, management, disaster.Kesiapsiagaan masyarakat dalam penanggulangan bencana merupakan penelitian kasus di lereng gunung Merapi bagian selatan di Kecamatan Cangkringan, Kabupaten Sleman. Penelitian ini bertujuan untuk menjawab persoalan: 1) bagaimana respon masyarakat dalam membangun kesiapsiagaan; 2) bagaimana eksistensi kesiapsiagaan masyarakat. Data dan informasi dihimpun dari beberapa sumber dengan teknik;a) studi dokumentasi; b) wawancara mendalam; c) observasi; dan d) diskusi kelompk terarah. Dari analisis deskriptif kualitatif terungkap bahwa masyarakat di lereng gunung berapi, umumnya mempunyai metode pemecahan masalah (coping strategy) dan nilai yang mendasari perilaku masyarakat berhubungan dengan alam. Masyarakat dan pemerintah telah bersatu untuk mencapai kemaslahatan manusia. Aksi Cangkringan merupakan bukti; 1) keseriusan negara dalam pengurangan risiko bencana; 2) konsistensi dan pertanggungjawaban Negara Republik Indonesia atas kesepakatan ASEAN, Asian dan bangsa bangsa dunia dalam pengurangan resiko bencana. Model kesiapsiagaan masyarakat di Cangkringan dapat direplikasi di lokasi lain yang mempunyai tingkat kerawanan cukup tinggi. Namun dalam kerangka replikasi model tersebut, alokasi waktu dan tenaga dari masyarakat perlu dijadikan bahan pertimbangan. Masyarakat lereng gunung umumnya tidak mempunyai pendapatan tetap, sehingga mereka perlu kompensasi atas waktu dan tenaga yang seharusnya produktif untuk diri dan keluarganya tersita untuk mengikuti berbagai program.Kata Kunci: kesiapsiagaan, masyarakat, penanggulangan bencana